2013
DOI: 10.1063/1.4816467
|View full text |Cite
|
Sign up to set email alerts
|

Anthrax toxin-induced rupture of artificial lipid bilayer membranes

Abstract: We demonstrate experimentally that anthrax toxin complexes rupture artificial lipid bilayer membranes when isolated from the blood of infected animals. When the solution pH is temporally acidified to mimic that process in endosomes, recombinant anthrax toxin forms an irreversibly bound complex, which also destabilizes membranes. The results suggest an alternative mechanism for the translocation of anthrax toxin into the cytoplasm. [http://dx

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 128 publications
(158 reference statements)
2
39
0
Order By: Relevance
“…However, an alternative model has been proposed based on membrane rupture. Using artificial lipid bilayers and physiological pH gradient (5.5/7/2) of endosomal acidification, it has been observed that LF or EF irreversibly binds to PA channels leading to disruption of the membrane and release of PA-LF or PA-EF complexes which are enzymatically active [116].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, an alternative model has been proposed based on membrane rupture. Using artificial lipid bilayers and physiological pH gradient (5.5/7/2) of endosomal acidification, it has been observed that LF or EF irreversibly binds to PA channels leading to disruption of the membrane and release of PA-LF or PA-EF complexes which are enzymatically active [116].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…On the other hand, the host cell chaperones Hsp90 and the peptidyl-prolyl cis/trans isomerase cyclophilin A were reported to be critical for membrane translocation of the active moieties of clostridial C2, iota, and CDT toxins but not for LF of the anthrax toxin [368,369,370]. Provided that the corresponding bilayer measurements show successful translocation events similar to those described for the anthrax toxin, we believe these findings would add some useful arguments to the anthrax toxin uptake debate [18]. For that purpose, not only the native but also the PA 63 /C2I-His cross-combination of components could be tested.…”
Section: Discussionmentioning
confidence: 92%
“…To answer the fundamental question regarding the origin of the protein translocation driving force, the authors suggest that the PA 63 symporter achieves protein translocation using a tandem of two synergistic Brownian ratchets: the ϕ-clamp ratchet, promoting the substrate unfolding, and the charge-state ratchet, which biases the entry rates of the substrates into the pore. A conceptually different model of anthrax toxin translocation was recently suggested by Nablo and colleagues [46]. The model proposes that instead of the active components being threaded through the pore, anthrax toxin complexes (namely, LF or EF bound to the PA 63 channel) rupture membranes.…”
Section: Anthrax Toxin Of B Anthracismentioning
confidence: 98%